(untitled) (At-Tibyan, 2023)
This research is motivated by a reality that is concerning and requires attention, namely to help people and Indonesian people or others who feel they need it. God willing, the fact is that there may be more and more Indonesian and Southeast Asian Muslim communities who yearn for the presence of books of Al-Qur’an Interpretation of this kind, to accompany the existing Al-Qur’an commentary/books, bearing in mind on the one hand it is very possible that the existing interpretation is considered to still not provide adequate answers to all the things and problems they are looking for and questioning, while on the other hand, there have also been many changes in circumstances between the past and the present so that it requires the presence of interpretation which are seen as more in line with current developments. The research approach that the author uses is a library research approach, namely collecting information from reference books and studying these materials. The data obtained from the research were compiled and explained for further analysis based on the existing theory and then conclusions were drawn. So in outline, the research method is included in the category of qualitative research methodology. From the results of the study it can be concluded that: based on what the author has searched for and knows that Al-Amin’s interpretation of the dissection of surah Al-Fatihah is in the style of fiqh interpretation and the method used is the tahlili method and the idea of interpretation is up to date.